Cardiac abnormalities in chronic progressive external ophthalmoplegia. Issue 5 (May 1976) - McComish, M; Compston, A; Jewitt, D
Abstract : This report describes heart disease in a 32-year-old man with the syndrome of chronic progressive external ophthalmoplegia (CPEO). The surface electrocardiogram showed first degree AV block and left bundle-branch block and there was HV prolongation on the His bundle electrogram. Endomyocardial biopsy showed the changes of hypertrophy on light microscopy, and on electron microscopy there were increased numbers of mitochondria which appeared structurally normal. A permanent demand pacemaker was inserted because these patients are prone to develop complete heart block.